Early cardiac contractility outcome of reoperative coronary artery bypass grafting using right gastroepiploic artery. Issue 11 (8th August 2021) - Shiraishi, Manabu; Kimura, Naoyuki; Yamaguchi, Atsushi
Abstract: Background and aim of the study: Reoperative coronary artery bypass grafting (redo CABG) still carries higher mortality and increased morbidity compared with primary CABG. In this study, we retrospectively reviewed our operative outcome of redo CABG to evaluate the impact of the left anterolateral thoracotomy approach using the right gastroepiploic artery (RGEA). Methods: Between 1994 and 2020, 11 patients (mean age 60.3 ± 13.1 years; nine men, two women) underwent isolated redo CABG using the RGEA via the left anterolateral thoracotomy. Results: The mean duration from the initial CABG was 128.3 ± 88.4 months. Redo CABG was performed because of graft occlusion in six patients (54.5%), graft stenosis in one patient (9.1%), and progressive disease of previously ungrafted vessels in four patients (36.4%). The total number of bypasses using RGEA (including Y‐composite vein grafts) was 16 (four left anterior descending branches, two diagonal branches, five circumflex branches, five right coronary arteries). No residual graft injury, major comorbidity, or in‐hospital death was observed. Changes in echocardiographic values before and after redo CABG were 210.9 ± 48.2 ml and 175.0 ± 41.4 ml in left ventricular end‐diastolic volume, 130.2 ± 49.2 ml and 94.4 ± 33.0 ml in left ventricular end‐systolic volume, and 45.6 ± 11.0% and 52.2 ± 10.7% in left ventricular ejection fraction, respectively. These parameters significantly improved after redo CABG. Conclusions: Redo CABG with RGEA grafting via the left anterolateral thoracotomy approach is a safe and effective surgical procedure especially in improving cardiac contractility in patients who required revascularization.